İdari birimlerde çalışan personellerin duygusal zekâ düzeyleri ile duygusal emekleri arasındaki ilişkinin incelenmesi : bir özel hastane örneği - Tat, Ramazan (My University, 2023)
Amaç: Bu çalışmanın amacı, özel bir hastanenin idari birimlerinde çalışan personelin duygusal zekâ düzeyi ile duygusal emekleri arasındaki ilişkiyi ortaya koymaktır. Gereç ve Yöntem: Kesitsel tipte tanımlayıcı çalışmanın amacı doğrultusunda, örneklem grubunu İstanbul’da özel bir hastanenin idari birimlerinde çalışan 190 personel oluşturmuştur. Veri toplama aracı olarak Rotterdam Duygusal Zekâ Ölçeği ve Duygusal Emek Ölçeklerini içeren bir anket kullanılmıştır. Araştırmada elde edilen veriler PSPP 1.6.2 kullanılarak analiz edilmiştir. Bulgular: Cinsiyet ve deneyim süresi için duygusal emek boyutlarında, yaş ve mesleği isteyerek seçip seçmeme değişkenlerine göre de duygusal zekâ boyutlarında anlamlı farklılık tespit edilirken medeni durum, eğitim ve çalışma süresi değişkenlerine göre de herhangi bir boyutta anlamlı farklılık tespit edilememiştir. Duygusal zekânın duygusal emek ile düşük düzeyde pozitif yönde ilişkili olduğu saptanmıştır. Sonuç: Sağlık sektöründe bulunan meslekler, sektörün yapısından dolayı yoğun hasta iletişimi ile duygusal zekâ ve duygusal emek gösterimi gerektirmektedir. Gelecekte farklı illerde, farklı sağlık kurumlarında daha fazla sayıda sağlık personelini kapsayacak şekilde planlanması daha güvenilir sonuçlara ulaşılmasını sağlayabilir.

Objective: The aim of this study is to reveal the relationship between emotional intelligence level and emotional labor of the personnel working in the administrative units of a private hospital. Materials and Methods: In line with the purpose of the cross-sectional descriptive study, the sample group consisted of 190 personnel working in the administrative units of a private hospital in Istanbul. A questionnaire including the Rotterdam Emotional Intelligence Scale and the Emotional Labor Scales was used as a data collection tool. The data obtained in the study were analyzed using PSPP 1.6.2 program. Explanatory factor analysis was applied to determine the construct validity of the scale. Findings: Significant differences were found in the dimensions of emotional labor for gender and experience duration. According to the variables of age and whether to choose the profession willingly, a significant difference was found in the dimensions of emotional intelligence. However, according to the variables of marital status, education and working time, no significant differences in any dimension could be determined. It has been found that emotional intelligence is positively associated with emotional labor at a low level. Conclusion: Professions in the health sector require intensive patient communication and emotional intelligence and emotional labor due to the structure of the sector. In the future, planning to include a greater number of health personnel in different provinces and different health institutions can lead to more reliable results.
Examination of the relationship between emotional intelligence levels and emotional labor of personnel working in administrative units : an example of a prıvate hospital
Keywords: Çalışan motivasyonu; Çalışanlar; Duygusal emek Emotional intelligence; Duygusal zeka; Duygusal zekâ; Emotional intelligence; Emotional labor; Employee motivation; Employees; Personel; Personnel; Psikolojik yönleri; Psychological aspects